Impact of Oxygen Saturation on Mortality in Obese and Non-obese Critically Ill Patients With Mechanical Ventilation: A Retrospective Observational Study - Li, Tong; Zhou, Dawei; Zhao, Dong; Lin, Qing; Wang, Dijia; Wang, Chao; Zhang, Rongli (Frontiers in Medicine, 2022)
Background The main objective was to evaluate the effect of oxygen saturation on mortality in critically ill patients with mechanical ventilation according to obesity status. Methods We conducted a retrospective observational study of mechanically ventilated patients admitted to the ICU. Demographic, arterial blood gas, ventilator setting, interventions, and peripheral oxygen saturation (Spo2) during the first 24h were recorded and compared between obese and non-obese patients. The main exposure was Spo2, time-weighted mean Spo2 (TWM-Spo2) and proportion of time spent in different Spo2 (PTS-Spo2) levels were calculated. The primary outcome was hospital mortality. Multivariable logistic regression models were performed to assess the relationship between Spo2 and mortality, and interaction between PTS-Spo2 and obesity status was explored. Results A total of 25,100 patients were included, of which 10,564 (42%) were obese patients. After adjusting for confounders, compared with TWM-Spo2 of 94-98%, TWM-Spo2 of <= 88% (OR 3.572; CI [2.343, 5.455]; p < 0.001) and of 89-93% (OR 1.514; CI [1.343, 1.706]; p < 0.001) were both associated with higher risk of hospital mortality. PTS-Spo2 of 99-100% was associated with increased risk of mortality for obese patients (OR 1.028; 95% CI 1.010-1.046; p = 0.002; Pinteraction= 0.001), while PTS-Spo2 of 89-93% was associated with increased risk of mortality (OR 1.089; 95% CI 1.051-1.128; p < 0.001; Pinteraction= 0.001) for non-obese patients. Conclusions For obese and non-obese critically ill patients with mechanical ventilation, the impact of oxygen saturation on hospital mortality is different.